Pemikiran Kritis Lucy Irigaray dalam Linguistik - Pudjiati, Danti (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
This article is aimed to introduce a contemporary philosopher women from France named Luce Irigaray.She becomes well known as critisizing all of the written in public are rare to discuss about women significanlly.One of her studies Is in linguistics entilled Je, tu, nous, Pour une Culturede la difference arguing about sex and gender in language. She examined the women do not be the subjectin the language Instead of men. Furthermore, feminine pronoun is replaced for unimportant things whereas masculine pronounIs for Important thing based on French culture. She thinks language has a essensial role as a means of communicationIn society and determined the position of women.